2010
DOI: 10.21273/hortsci.45.9.1345
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Mechanisms of the Yellow Vine Syndrome Development in the American Cranberry: Shade Effect

Abstract: Yellow vine symptoms are often observed in cranberry bogs. To explore the mechanisms of the formation of yellow vine syndrome in cranberry leaves, the shade effect on the chlorophyll (Chl) content and photosynthetic activities in cranberry bogs were investigated by spectrometric, high-performance liquid chromatography (HPLC), and in vivo Chl fluorescence kinetics. Spectrometric and HPLC analyses revealed that the yellow vine leaves were associated with a 11% ± 5% and 14% ± 5% increase in Chl a/ Chl b ratio aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Similar behavior was observed in Camellia leaves with development of an energy pipeline model of the photosynthetic apparatus [51,52]. In addition, the "Area" above the fluorescence transient for the shaded sample was also increased drastically, indicating the presence of a larger quinone pool [34,53]. To clarify the discrepancy between the chlorophyll fluorescence assay and chlorophyll determination by the spectrometric and HPLC method, a three-week chlorophyll fluorescence experiment was conducted.…”
Section: Unshaded Yellow Vine Leavesmentioning
confidence: 52%
See 3 more Smart Citations
“…Similar behavior was observed in Camellia leaves with development of an energy pipeline model of the photosynthetic apparatus [51,52]. In addition, the "Area" above the fluorescence transient for the shaded sample was also increased drastically, indicating the presence of a larger quinone pool [34,53]. To clarify the discrepancy between the chlorophyll fluorescence assay and chlorophyll determination by the spectrometric and HPLC method, a three-week chlorophyll fluorescence experiment was conducted.…”
Section: Unshaded Yellow Vine Leavesmentioning
confidence: 52%
“…The chlorophyll content of the yellow vine samples in the absence and presence of shade was determined by spectrometric analysis (Table 1). Shading increased Chl a and Chl b content by 11.1% and 13.9%, respectively [34]. HPLC analysis of shaded and unshaded yellow vine leaves using a C18 column with a photodiode array detector, following published procedures, was conducted and confirmed the spectrometric data.…”
Section: Effect Of Shade Treatmentmentioning
confidence: 61%
See 2 more Smart Citations
“…It is hypothesized that the yellow vine symptoms may be caused by nutritional imbalance and water stress (DeMoranville et al, 2009). The effect of shade treatment on yellow vine syndrome in cranberry bogs revealed that the shading of cranberry plants appears to reduce the syndrome by improving the photosynthetic activity and increasing the Chl content (Wei et al, 2010). The yellow vine leaves were associated with 11% ± 5% and 14% ± 5% increase in Chl a/Chl b ratio after shading, respectively.…”
Section: Resultsmentioning
confidence: 99%